AUTOMATED METHODS FOR SOLVING LINEAR PROGRAMMING PROBLEMS - S. Khaidarova (International Journal of Innovations in Engineering Research and Technology, 2022)
This article discusses the issues of using Simplexwin and Optimal 2 programs in solving linear programming problems